A causal model to prioritise the task of work packages in R&D projects. (19th September 2022) - Ramanathan, M.; Punniyamoorthy, M.; Balamurugan, V.; Ravi, B.I.
Evaluation of research and development (R&D) project is important for prioritising the tasks that are vital for the success of projects. In this paper, the work breakdown structure (WBS) principle has been applied to convert the R&D projects of the Defence Research and Development Organisation (DRDO) in India into a number of work packages. The DRDO projects are classified into five groups, and under each group, there are some 11 common work packages identified to complete the projects. Each work package consists of metrics and prioritising these metrics is important to concentrate on these important metrics as it is a project success criterion. A causal model has been developed in this paper for this purpose. An instrument has been developed, and the data were collected through a survey from 179 senior scientists of DRDO. Based on the results of the causal model developed, the metrics have been ranked from the work packages based on their respective complexity. The ranking of metrics in each work packages can help the project in-charge of any project in tactical and operational level activities down the line. The methodology adopted in this paper can be extended for the projects of such a similar nature.